Efficacy of chlorin dioxide wipes in disinfecting airway devices contaminated with Covid-19 - Albaharna, Hussain; Almubiereek, Hassan; Almualim, Mohammed; Bukhamsin, Rehab; Abdelfattah, Ahmed; Buohliqah, Lamia (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Reprocessing and disinfecting endoscopes is a routine practice in otolaryngology. An effective, safe, and rapid disinfection technique is essential during the COVID-19 pandemic Objective: To validate the efficacy of chlorine dioxide wipes in disinfecting three types of airway endoscopes contaminated with COVID-19-positive patient secretions. Methods: Chlorine dioxide wipes were tested on rigid nasal endoscopes, laryngoscope blades, and flexible bronchoscopes. The endoscopes were disinfected using the wipes after exposure to COVID-19-positive patients. The tested scope was included in the study if the post procedure pre disinfection swab was positive for COVID-19 virus using RT-PCR. We analyzed 38 samples for 19 subjects (scopes) pre and post disinfection with chlorine dioxide wipes from July 2021 to February 2022. Results: A total of four rigid endoscopes, four flexible bronchoscopes, and four laryngoscopes were included in the study which represent 24 pre and post disinfection swabs. The others were excluded because of negative pre disinfection swab. All the post disinfection PCR swab results were negative. Conclusions: Chlorine dioxide is a convenient, fast, and effective disinfection technique for COVID-19-contaminated airway endoscopes.